Acúmulo do alumínio em derivados de trigo (Triticum aestivum) - Mello, Jéssia Carneiro de (2020)
Food consumption with significant levels of aluminum has been the focus of discussions related to health. The Brazilian legislation does not establish a limit for aluminum residues for food, neither the operational recommendations to ensure low concentrations of this metal and the official parameters limited to the daily consumption recommendations. Aluminum is distributed in nature, and can be present in raw materials or be the result of food production processes. In the wheat and its derivatives chain, exposure to metal occurs at planting, due to the presence of aluminum in the soil, as a result of leaching. However, the presence of this metal in cultivable soils represents low productivity, since this compound gives toxicity to plants, and as a result, an alternative such as liming, is used to minimize these effects, without, however, clarifying the potential migration of aluminum from the soil to edible parts of the plant, such as grains. A second critical step for the potential increase of aluminum in this chain is storage, a period in which the grains can be chemically treated with aluminum phosphide (phosphine) for pest control, and which may show residual metal accumulation. Based on this, two experiments were carried out: the first with the purpose of evaluating the effect of liming soil correction on the total aluminum content of wheat flour products and the second to evaluate the purge in the treatment of stored wheat grains as potential contributing to the increase of aluminum in its derivatives. For this, wheat was planted in soil with presence and without liming, in a no-tillage system, followed by experimental grinding of grains to obtain derivatives: white wheat flour, whole-wheat flour and bran. In the second experiment, a doping of wheat grains was performed with dosages of 0, 50, 100 and 200% of the phosphine residual in tablets, followed by experimental grinding to separate the same derivatives from the first experiment. The concentration of aluminum in the flour products was carried out by the ICP-MS method. The results showed that the total aluminum present in wheat flour products may be due to a sum of sources along the production chain, and that the contamination is present in a greater quantity in the bran than in flour. In this way, it is concluded that the increase of aluminum due to its presence in the soil or the use of chemicals in pest control is considerable, however, this is not entirely inevitable, since preventive measures can be adopted, such as liming and good practices in the chemical treatment of stored grains, to ensure that residuals are kept to a minimum.